Optimizing Raytracing Algorithm Using CUDA - Sayed Ahmadreza Razian; Hossein MahvashMohammadi (Emerging Science Journal, 2017)
Now, there are many codes to generate images using raytracing algorithm, which can run on CPU or GPU in single or multi-thread methods. In this paper, an optimized algorithm has been designed to generate image using raytracing algorithm to run on CPU or GPU in multi-thread algorithm.This algorithm employs light with depth of 8 to generate images. It is optimized by changing pixel travel priority and ray of light to thread, dedicating depth function to empty threads, and using optimized functions from MSDN library. Its code has been written in C++ and CUDA. In addition, we do the following to show its performance: comparing implementation in different compiler mode, changing thread number, examining different resolution, and investigating data bandwidth.The results show that one can generate at least 11 frames per second in HD (720p) resolution by GPU processor and GT 840M graphic card, using trace method. If better graphic card employ, this algorithm and program can be used to generate real-time animation.